PENGARUH KECERDASAN INTRAPERSONAL TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SMP NEGERI DI KABUPATEN KOTABARU - Rahmi Yuliana (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2021)
The factors that influence student achievement are generally divided into two parts, namely external factors and internal factors. But the focus of this research is internal factors, especially psychological factors, namely intrapersonal intelligence. This study aims to analyze how much influence intrapersonal intelligence has on students' mathematics learning achievement at SMP Negeri in Kotabaru Regency. This type of research is quantitative research with ex-post facto methods. The population in this study were all students of Class IX of State Junior High Schools in Kotabaru Regency. The sample in this study were 44 students of class IX of SMP Negeri accredited A and B. The sampling technique was carried out using purposive sampling. The instrument used in this study was the intrapersonal intelligence scale. Based on the results of research conducted on grade IX students at 14 junior high schools in Kotabaru Regency who have been accredited A and accredited B, it shows that there is a relationship between intrapersonal intelligence and student achievement. Students who get good learning achievement will have high intrapsonal intelligence.